2022
DOI: 10.1029/2022wr032041
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed Urban‐Stormwater Control Improved Stream Water Quality in a Catchment‐Scale Experiment

Abstract: The code comprises source code for the manuscripts, figures and tables as Rmarkdown documents, including several purpose-written functions specific to the data. The data and code will be permanently archived if the paper is accepted for publication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 62 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…But the small size of the response in our lowest EI sites, with 4% EI, confirms that even a very small degree of catchment stormwater impacts can limit instream community assembly (King & Baker, 2011; Walsh & Webb, 2016). Larger responses to restoration of instream habitat heterogeneity are only likely to be achieved in streams without urban impacts or with high‐performing urban stormwater control measures that intercept runoff from nearly all upstream impervious surfaces (e.g., Walsh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the small size of the response in our lowest EI sites, with 4% EI, confirms that even a very small degree of catchment stormwater impacts can limit instream community assembly (King & Baker, 2011; Walsh & Webb, 2016). Larger responses to restoration of instream habitat heterogeneity are only likely to be achieved in streams without urban impacts or with high‐performing urban stormwater control measures that intercept runoff from nearly all upstream impervious surfaces (e.g., Walsh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The primary evidence comes from streams that have at least in part been protected from catchment urbanization by informal stormwater drainage (Walsh, 2004) or by extensive dispersed stormwater control (Hopkins et al, 2022). We are not aware of robust studies that have demonstrated restoration of biotic assemblages through catchment stormwater control, but restoration of water quality and hydrology after stormwater retrofit brings hope that this may be effective (Walsh et al, 2022). However, in existing urban landscapes, the availability of appropriately located land for stormwater control measures and the lack of demand for stormwater harvesting to reduce runoff volumes remain challenging problems in most existing policy settings.…”
Section: Setting Expectations and Priorities For Urban Stream Managementmentioning
confidence: 99%
“…Pennino et al [115] indicate that the use of stormwater green infrastructure brings a significant reduction in flash hydrology and pollution concentration. SCMs reduce the concentration of phosphorus [116,117], and they can limit, delay, or stabilize the supply of nitrogen [115,[118][119][120]; in the case of suspension, no influence on their reduction is shown [115,116], but of course it depends on the type of SCMs, their location, and the scale of the solutions used [115,118,119]. A study by Walsh et al [116] showed that extensive use of dispersed SCMs can reverse the negative effects of urbanization and improve stream water quality.…”
mentioning
confidence: 99%
“…SCMs reduce the concentration of phosphorus [116,117], and they can limit, delay, or stabilize the supply of nitrogen [115,[118][119][120]; in the case of suspension, no influence on their reduction is shown [115,116], but of course it depends on the type of SCMs, their location, and the scale of the solutions used [115,118,119]. A study by Walsh et al [116] showed that extensive use of dispersed SCMs can reverse the negative effects of urbanization and improve stream water quality. Therefore, it seems advisable to introduce administrative recommendations (or even an obligation) to apply stormwater control measures for all new investments, as well as to strengthen their implementation through economic instruments, such as rainwater charges and investment co-financing.…”
mentioning
confidence: 99%